Association between tea intake and hospitalized nephrolithiasis in Chinese adults: A case–control study - Liu, Yingyu; Bi, Shiyuan; Li, Hexiao; Shi, Jianxiu; Xia, Yang; Niu, Kaijun; Bai, Song (Frontiers in Nutrition, 2022)
Introduction and aim: Nephrolithiasis is one of the most common urological disorders worldwide. Tea is one of the most popular drinks worldwide. This study aimed to explore the association between tea intake and hospitalized nephrolithiasis in Chinese adults. Methods: The patients and healthy participants were from the Shenyang sub-cohort of Tianjin Chronic Low-Grade Systemic Inflammation and Health Cohort Study. After selecting and matching by age (± 1 year) and sex using the 1:2 ratio, 834 participants were included in this study. Of these, 278 patients had hospitalized nephrolithiasis and 556 were healthy controls. The tea intake was assessed using a validated self-administered food frequency questionnaire. Multivariate conditional logistic regression analysis was used to evaluate the association between tea intake and hospitalized nephrolithiasis. Results: After adjustment, a higher frequency of tea intake was found to be negatively associated with the risk of hospitalized nephrolithiasis. Compared with participants who never drank tea, the odds ratio (95% confidence interval) [OR (95% CI)] for participants who drank ≥1 cup (180 mL) of tea per day was 0.418 (0.192–0.911) (P for trend = 0.013). Moreover, the adjusted OR (95% CI) for participants who drank ≥1 cup of green tea and black tea per day was 0.189 (0.069–0.520) (P for trend <0.001) and 1.248 (0.437–3.559) (P for trend = 0.654), respectively. Conclusions: Increased tea intake was found to be associated with a lower risk of hospitalized nephrolithiasis among Chinese adults. This finding may assist in the prevention of hospitalized nephrolithiasis.